2013
DOI: 10.1152/ajpheart.00309.2013
|View full text |Cite
|
Sign up to set email alerts
|

The decrease of cardiac chamber volumes and output during positive-pressure ventilation

Abstract: Positive-pressure ventilation (PPV) is widely used for treatment of acute cardiorespiratory failure, occasionally at the expense of compromised cardiac function and arterial blood pressure. The explanation why has largely rested on interpretation of intracardiac pressure changes. We evaluated the effect of PPV on the central circulation by studying cardiac chamber volumes with cardiac magnetic resonance imaging (CMR). We hypothesized that PPV lowers cardiac output (CO) mainly via the Frank-Starling relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
(50 reference statements)
1
23
0
5
Order By: Relevance
“…Manoeuvres triggering pulmonary hypertensive crises such as insufficient sedation, rise of pCO 2 or suctioning should be avoided. Moreover, positive pressure ventilation impairs cardiac filling and output22 especially in the failing RV. Normoventilation (pCO 2 -levels 35–40 mm Hg) and long expiratory times are recommended.…”
Section: Therapy Of Acute Ph In the Icumentioning
confidence: 99%
“…Manoeuvres triggering pulmonary hypertensive crises such as insufficient sedation, rise of pCO 2 or suctioning should be avoided. Moreover, positive pressure ventilation impairs cardiac filling and output22 especially in the failing RV. Normoventilation (pCO 2 -levels 35–40 mm Hg) and long expiratory times are recommended.…”
Section: Therapy Of Acute Ph In the Icumentioning
confidence: 99%
“…Mechanical ventilation, especially positive end-expiratory pressure, decreases the blood volume in the intrathoracic vascular bed and heart, and decreases cardiac filling and cardiac output via the Franck-Starling relationship 64,65. In fact, mechanical ventilation decreases right ventricular preload (venous return), and increases right ventricular afterload (pulmonary vascular resistance) and left ventricular afterload.…”
Section: Perioperative Blood Pressure Controlmentioning
confidence: 99%
“…In a small study done in infants on highfrequency oscillatory ventilation showed no adverse effects as compared to controls [27] . The effect of positive pressure ventilation on the cardiac output and cardiac volumes have been found to be significant in agreement with the FrankStarling law [28] and this must be taken into consideration while evaluating donor hearts by cardiac MRI. Considering the versatility of cardiac magnetic resonance imaging (CMRI) in assessing cardiac function and its feasibility in mechanically ventilated patients cardiac MRI protocols need to be instituted and actively used in evaluating donor hearts.…”
Section: Contrast Enhanced 2d and 3d Echocardiographymentioning
confidence: 66%